Incidence of non-01 Vibrio cholerae and Aeromonas spp. in fresh water in Araraquara, Brazil - Falcao, D. P.; Lustri, W. R.; Bauab, Taís Maria [UNESP] (Springer, 1998)
The occurrence of Aeromonas spp., Vibrio cholerae, and Plesiomonas shigelloides in fresh water from various sources in Araraquara, State of São Paulo, Brazil was determined. Samples from ten distinct irrigation systems used in vegetable cultivation, from five distinct streams, from two reservoirs, from one artificial lake, and from three distinct springs were analyzed. All isolates were serotyped and tested for hemolysin, cytotoxin, heat-stable (ST) and heat-labile (LT) enterotoxins production; presence of plasmid; autoagglutination and drug resistance. V. cholerae isolates were also tested for cholera enterotoxin (CT) production, and Aeromonas isolates for suicide phenomenon. No P. shigelloides was found. V. cholerae non 01 was found in five irrigation water samples and in three stream samples. Aeromonas sp. were isolated in two samples of irrigation water, in three streams, and in one reservoir. All the V. cholerae and Aeromonas isolates were positive for P-hemolysin production, and all Aeromonas isolates were positive for suicide phenomenon; cytotoxic activities were observed in two Aeromonas strains. Cholera enterotoxin was not found in eight V. cholerae non-01 isolates tested by the Y-1 mouse adrenal cell. All isolates were also negative for the other virulence markers. Ii cholelerae isolates were found to be sensitive to the majority of drugs tested, while Aeromonas strains presented multiple drug resistance..